The Ethical and Mythological Core of Culture - Viktoriia Larionova (Vasyl Stefanyk Precarpathian National University, 2019)
The purpose of this research is to discuss the role of myth in human culture, to define and specify its main functions. The goal is to show that being part of a cultural heritage, myths are an essential part of human culture in any epoch. Mythology provides a true reflection of the moral values of society and aesthetic attitude to reality. Mythological consciousness is the oldest form of understanding and comprehension of the world, nature, society and people, the oldest system of values. There exists a direct connection between mythological and historical forms of consciousness. Mythology as a science enhances the research process and allows for the extension of knowledge into other fields, the humanities in particular. It performs the function of explanation and legitimation of social norms. Myth-making is a property of human consciousness. Myths as products of primary forms of thinking, the oldest forms of consciousness retain their role in all epochs; created and maintained by all generations, they have been preserved throughout millennia.